Outcome of grand multi-gravidity & multiparity A retrospective study - Akther, Rabeya (Journal of Dhaka Medical College, 2013)
Objective: To examine the obstetric outcome in grand multi-parous and the effect of high parity among young women, aged 18-34 years vs. older women, aged 35years and above. Methods: This is a retrospective study done in DMCH from 1st August 2007 to 31st August 2008. For study purpose 98 patients were selected randomly whose gravidity 6th and more. To see peri-natal outcome, the cut-off point of 28 weeks was taken. Results: Mean age of the study group was 32(22-45) years. Mean gravidity and parity of the study group was 6.7 (6-11) and 4(1-8) respectively. Ninety percent pregnancy affected by different complications. Hypertensive disorder of pregnancy (14.3%) and ante-partum hemorrhage (14.3%) was more common. Bad obstetric history (12.35%), mal-presentation (11.23%) and intra-partum complications were also common. Twenty two percent (22.46%) pregnancies complicated by gestational diabetes, maternal medical disease and multi-fetal gestation. Regarding fetal outcome, peri-natal loss was 10(14%). Preterm delivery, ante partum hemorrhage, bad obstetric history, gestational diabetes and mal presentation were the cause of peri natal loss. Lack of reproductive knowledge, unmet need for contraception, poor obstetric performance and too early marriage are the main cause of grand multi-gravidity and multi-parity Conclusion: Diabetes mellitus, hypertension, ante partum hemorrhage, mal-presentation was more common in grand multi-parous irrespective of age. There was no significant difference in the incidence of obstetric complications and in perinatal outcome among both groups. DOI: http://dx.doi.org/10.3329/jdmc.v22i1.15629 J Dhaka Medical College, Vol. 22, No. 1, April, 2013, Page 67-71